1998
DOI: 10.2136/sssaj1998.03615995006200030034x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Abundance of Nitrogen‐15 in a Forest Soil

Abstract: Because of measurement difficulties, only a few studies on natural 15N abundance (δ15N) of inorganic N in forest soil have been pursued despite its importance for interpretations of plant δ15N signatures. To investigate stable N isotope ratios in inorganic N, the δ15N values and concentrations of total N, NH+4‐N, and NO−3‐N of forest mineral soils in four profiles were measured along a slope (altitude of 765–870 m) in a coniferous (Japanese red cedar, Cryptomeria japonica D. Don) forest in Japan. Generally, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
61
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 0 publications
12
61
2
Order By: Relevance
“…Where studies have shown net rates of N mineralization and nitrification to vary among hillslope positions in forest soils, higher rates occurred at footslope locations (Hiroto and Haibara 1994;Koba et al 1998). In WS1, there is little evidence to suggest that net nitrification rates are different at the higher and lower elevation sites (Owen et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where studies have shown net rates of N mineralization and nitrification to vary among hillslope positions in forest soils, higher rates occurred at footslope locations (Hiroto and Haibara 1994;Koba et al 1998). In WS1, there is little evidence to suggest that net nitrification rates are different at the higher and lower elevation sites (Owen et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The limited data available (Koba et al 1998; suggest that measurements of the isotopic composition in both soil extractable pools and soil solution NO 3 and NH 4 could contribute to understanding regional differences in rates and patterns in N cycling. Currently there are no measurements of the N stable isotope composition of atmospheric inputs, soil solution or denitrification products available for forests in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination that occurs against the heavier N isotope ( 15 N) during mineralization and nitrification of organic N compounds should lead to the following enrichment patterns in δ 15 N signatures in labile soil N pools: organic N ≥ NH 4 + > NO 3 -, at least under low N conditions (Nadelhoffer & Fry, 1994;Koba et al , 1998). However, the diversity of soil N pools and processes can lead to more complex patterns of pool labeling, for example high nitrification rates can enrich NH 4 + pools relative to soil organic matter (Koba et al , 1998;Hobbie et al , 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, the diversity of soil N pools and processes can lead to more complex patterns of pool labeling, for example high nitrification rates can enrich NH 4 + pools relative to soil organic matter (Koba et al , 1998;Hobbie et al , 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In temperate forest soil, 8 15 N values in soil largely depended on net nitrification (Koba et al 1998), while in highly weathered tropical soils, these values resulted from the selective losses of 15N-depleted nitrate associated with both nitrification and denitrification (Piccolo et al 1994).…”
mentioning
confidence: 99%